Multi-wavelength erbium/Raman gain based random distributed feedback fiber laser - Sugavanam, S; Zulkifli, Mohd Zamani; Churkin, D V (IOP Publishing, 2015)
A multiwavelength generation in a random distributed feedback fiber laser based on hybrid Raman and erbium gain and a Lyot all-fiber spectral filter is demonstrated for the first time. The use of erbium-doped fiber allows a multi-wavelength generation to be achieved at lower pump powers in comparison with random fiber lasers based on Raman gain only. The operating bandwidth and flatness of power distribution between different lines in generation are also improved in the hybrid gain configuration.